1997
DOI: 10.1007/s001250050638
|View full text |Cite
|
Sign up to set email alerts
|

Renal antioxidant enzyme mRNA levels are increased in rats with experimental diabetes mellitus

Abstract: Although the pathophysiology of diabetic complications is probably multifactorial, the results of in vitro [1], animal [2], and human [3] studies suggest a role for oxidative stress via an increased formation of free radicals. Increased generation of reactive oxygen metabolites such as superoxide anion and hydrogen peroxide has been shown to occur in diabetes mellitus in association with hyperglycaemia [4]. An increased glucose concentration can induce formation of free radicals and activation of oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
45
1
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 47 publications
3
45
1
1
Order By: Relevance
“…In response to oxidative stress, antioxidant enzymes are induced to protect cellular and tissue injury (18,19,27). Although Cu/Zn SOD and catalase mRNA levels have been shown to be significantly induced in the total kidney of untreated diabetic rats (18), we were not able to find any change in mRNA content of Cu/Zn SOD, GPX, and catalase in glomeruli of diabetic rats (19).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In response to oxidative stress, antioxidant enzymes are induced to protect cellular and tissue injury (18,19,27). Although Cu/Zn SOD and catalase mRNA levels have been shown to be significantly induced in the total kidney of untreated diabetic rats (18), we were not able to find any change in mRNA content of Cu/Zn SOD, GPX, and catalase in glomeruli of diabetic rats (19).…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, involvement of oxidative stress has been indicated by the presence of lipid peroxidation products and 8-hydroxydeoxyguanosine in the kidney from streptozotocin (STZ)-induced diabetic rats (16,17). Regarding the defense system to oxidative stress, antioxidant enzymes such as catalase and Cu/Zn-superoxide dismutase (Cu/Zn-SOD) were found to be enhanced in kidneys of STZ-induced diabetic rats (18). However, it remains unknown whether these findings reflect a common consequence of the tissue damage in diabetic kidney or oxidative stress has a primary role in the pathogenesis of diabetic kidney disease.…”
mentioning
confidence: 99%
“…5 mmol/l = 1.0, (n = 5 independent experiments for fibronectin and collagen IV, n = 3 for collagen I and III) tured in high glucose concentrations [35]. Increases in CuZnSOD mRNA concentrations have also been reported in endothelial cells under similar conditions [35] and in diabetic rat kidneys [36]. These results show, for the first time, the ability of the VSMC to respond to glucose-induced oxidative stress by increasing the mRNA levels of the SOD enzymes (both CuZnSOD and MnSOD).…”
Section: Discussionmentioning
confidence: 80%
“…In contrast to the findings with SOD, neither high continuous glucose nor intermittent high glucose resulted in substantial induction of GPx or CAT activity in the retinal cells. Although we and others have shown that high glucose has been shown to induce GPx and CAT in many different cells and tissues [11,12,[32][33][34][35] , there is most certainly a divergent and perhaps cell-specific regulation of these antioxidant enzymes. Our lack of induction with GPx and CAT also fit well with similar findings in the retina of hyperglycemic animals [30] .…”
Section: Discussionmentioning
confidence: 80%